Incorporating Equity into Pedestrian Master Plans. Issue 10 (October 2020) - Berg, Amber; Newmark, Gregory L.
This research provides a framework for addressing inequities through municipalities' transportation plans, which have no federal equity requirements and have been given little guidance for incorporating equity. Fifteen pedestrian master plans are reviewed for their equity considerations to derive a tripartite framework for systematically incorporating equity into transportation plans, known as The Three A's of Equity. Acknowledgment recognizes equity as a value of the plan and that there are transportation inequities to be eliminated; Accountability establishes equity measures to be achieved by the transportation plan; and Application identifies the interventions that will be implemented to help achieve equity. Using the proposed framework, the 15 plans are evaluated for their equity considerations. The analysis finds that cities are increasingly including equity into their pedestrian master plans, but do so inconsistently, seldom include the Accountability element, and rarely include race in their equity considerations. The proposed framework, the Three A's of Equity, can guide cities in systematically incorporating equity into their transportation plans to ideally advance more equitable outcomes.